KOMPETENSI PROFESIONAL GURU PENDIDIKAN AGAMA ISLAM DALAM PENGELOLAAN KELAS DI SEKOLAH MENENGAH PERTAMA NEGERI 6 MUARO JAMBI - Rahmah, Almaida Mauliza; Hasanah, Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the professional competence of Islamic Religious Education (IRE) teachers in classroom management at State Junior High School 6 Muaro Jambi. The research focuses on the implementation of classroom management, the obstacles faced by teachers, and the strategies applied to overcome these challenges. This study employed a qualitative descriptive approach. Data were collected through classroom observations, interviews with Islamic Religious Education teachers, and documentation analysis. The results of the study indicate that the professional competence of IRE teachers in classroom management has been implemented fairly well, as reflected in efforts to create an orderly, comfortable, and conducive learning environment. Teachers demonstrated professional competence through classroom discipline management, the use of appropriate teaching methods, and persuasive approaches in handling students’ behavior. However, several obstacles were identified, including limited variation in teaching methods, classroom layout constraints, and students’ lack of focus during learning activities. To address these challenges, teachers applied various strategies such as adjusting teaching styles, utilizing instructional media, improving teacher–student communication, and providing continuous motivation. The study concludes that professional competence plays a crucial role in effective classroom management and significantly contributes to enhancing students’ learning engagement in Islamic Religious Education.